2012
DOI: 10.3389/fnhum.2012.00292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mindful-attention and compassion meditation training on amygdala response to emotional stimuli in an ordinary, non-meditative state

Abstract: The amygdala has been repeatedly implicated in emotional processing of both positive and negative-valence stimuli. Previous studies suggest that the amygdala response to emotional stimuli is lower when the subject is in a meditative state of mindful-attention, both in beginner meditators after an 8-week meditation intervention and in expert meditators. However, the longitudinal effects of meditation training on amygdala responses have not been reported when participants are in an ordinary, non-meditative state… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
221
4
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(241 citation statements)
references
References 134 publications
(204 reference statements)
11
221
4
5
Order By: Relevance
“…For example, Lieberman and colleagues ) demonstrated that asking participants to label their affective state activated the right pre-frontal cortex, thereby dampening the effect of the amygdala, or primitive brain. Desbordes et al (2012) also found reduced activity in the amygdala within a mindfulness group of practitioners when compared to a control group. The mechanism that de-activates one part of the brain to activate another is still under investigation, but there is sufficient evidence to show that some of these functions are physiologically binary.…”
Section: Intuitionmentioning
confidence: 89%
“…For example, Lieberman and colleagues ) demonstrated that asking participants to label their affective state activated the right pre-frontal cortex, thereby dampening the effect of the amygdala, or primitive brain. Desbordes et al (2012) also found reduced activity in the amygdala within a mindfulness group of practitioners when compared to a control group. The mechanism that de-activates one part of the brain to activate another is still under investigation, but there is sufficient evidence to show that some of these functions are physiologically binary.…”
Section: Intuitionmentioning
confidence: 89%
“…We propose that this excitatory activity is the result of widespread depolarization which is inhibited by slow, deep breathing and some types of meditation. Studies have found decreased activity in the amygdala during mindfulness meditation (Desbordes et al 2012) and during non-meditative states after mindfulness training (Desbordes et al 2012). This decrease in amygdala response, after meditation training, has been found in patients with social anxiety disorder (Goldin and Gross 2010) as well as healthy patients (Desbordes et al 2012;Taylor et al 2011).…”
Section: Possible Role Of Membrane Potential In Cardiorespiratory Modmentioning
confidence: 99%
“…Mindfulness training has also been shown to experimentally enhance both prefrontal and amygdala functioning 117,118 , and has been claimed to reduce aggression in offenders 119,120 . We caution that this potential for crime prevention is extremely preliminary, but logically follows from our review of biological risk factors, legal implications, and prevention measures.…”
Section: Intervention and Preventionmentioning
confidence: 99%